Unidirectional expansion of lattice parameters in GaN induced by ion implantation - 法涛 李琳 姚淑德 吴名枋 周生强 (Chinese physics B, 2011)
This paper reports that the 150-keV Mn ions are implanted into CaN thin film grown on A1203 by metalorganic chemical vapour deposition. The X-ray diffraction reciprocal spacing mapping is applied to study the lattice parameter variation upon implantation and post-annealing. After implantation, a significant expansion is observed in the perpendicular direction. The lattice strain in perpendicular direction strongly depends on ion fluence and implantation geometry and can be partially relaxed by post-annealing. While in the parallel direction, the lattice parameter approximately keeps the same as the unimplanted GaN, which is independent of ion fluence, implantation geometry and post-annealing temperature.